Moderating Effect of Regional Original Revenue on the Influence of the Number of Tourists on Regional Revenue and Expenditure Budget - I Nyoman Sutapa; Ni Putu Riski Martini; Ni Luh Putu Mita Miati (JASF: Journal of Accounting and Strategic Finance, 2018)
This study aims to provide empirical evidence about the effect of the number of tourists on the Regional Revenue and Expenditure Budget (APBD) with local original revenue (PAD) as moderating variable. The population in this study was at the Regency or City Government in Bali from 2008 to 2017. The testing tools used were Partial Least Square analysis - Structural Equation Modeling (PLS-SEM). The results of this study prove that the number of tourists has a significant positive effect on the APBD with PAD as moderator. The number of tourists has a positive and significant effect on PAD, PAD has a positive and significant effect on the APBD. While the direct influence between the number of tourists to the APBD is not significant